PEMBERIAN ASAM LEMAK TIDAK JENUH OMEGA 3 TERHADAP PENURUNAN KADAR ASAM URAT PADA PENDERITA ASAM URAT (GOUT) PASIEN RAWAT JALAN RSUP Prof. dr. R.D. KANDOU MANADO - Rudolf Boyke Purba (Jurnal GIZIDO, 2013)
Uric acid (gout) is characterized by uric acid levels were persistently elevated in the blood(hyperuricemia) having a concentration greater than 7 mg/dl in men and 6 mg/dl in women.Provision of unsaturated fatty acids Omega 3 can reduce inflammation and pain in the newjoint study on rheumatoid arthritis and osteoarthritis patients.The purpose of this study wasto determine the effect of food supplementation of unsaturated fatty acids Omega 3 todecrease uric acid levels in patients with uric acid (gout) in the outpatient department ofProf.dr. R.D. Kandou Manado. This research is a Clinical Trial with Non- randomized studydesigns quasi experimental Concurrent Control Trial (Non- Equivalent Control GroupDesign With Pre Test and Post Test). The treatment group was given food supplementsunsaturated fatty acids Omega 3 at a dose of 600 mg / day , and the control group was notgiven Omega 3, but given Vitamin E 100 g per day as a placebo. Samples were peoplewith gout/hyperuricemia (gout). The data collected by interview (characteristics of thesample) and uric acid levels (lab results) after 8 weeks of consuming omega 3. Dataanalysis using the t test and paired . The result there is a decrease in blood levels of uricacid in the treatment group (from 8.30 mg/dl to 7,28 mg/dl) when compared with the levelsof uric acid in the blood in the control group ( from 8.22 mg / dl to 8 , 64 mg/dl) . Changes inuric acid levels in the treatment group was statistically (Paired) had a difference (differencedecreases) were highly significant with a value of t = 5.832 (p = 0.000). Results ofstatistical tests (t test) of the differences in levels of uric acid in the two groups (treatmentand control) showed a significant difference with p = 0.004 (p < 0,05). Conclusions are theeffect of Omega 3 fatty acids to decrease uric acid levels .